Profiles of attitudes toward inclusive education among Chinese in-service teachers: their relationships with demographic factors and organizational commitment - Deng, Yuhao; Yuan, Wei; Zhang, Li-fang; Xie, Zhengli (Frontiers in Psychology, 2024)
The increased diversity of students (e.g., students with special educational needs) has presented teachers with unprecedented challenges. Teachers’ attitudes towards inclusive education play a crucial role in teachers’ organisational well-being. However, existing studies mostly explored attitudes towards inclusive education based on a variable-centred approach. This study used a person-centred approach to identify teachers’ attitude profile membership and explored the relationships of attitude profiles with demographic factors (i.e., gender, years of teaching experience, subject taught, and in-service training) and organisational commitment. Nine hundred and seventy-two in-service teachers from forty-nine inclusive education schools in Beijing participated in this survey. The latent profile analysis results revealed four attitude profiles: involuntary participation, behaviour avoidance, neutral, and proactive involvement. Years of teaching experience and in-service training were significant predictors of teachers’ latent profile membership. Among the four profiles, teachers belonging to the involuntary participation profile showed the highest levels of maladaptive commitments to inclusive education schools. Teachers belonging to the proactive involvement and the behaviour avoidance profiles showed higher levels of adaptive commitments. However, teachers belonging to the neutral profile had the lowest levels of adaptive commitments. The theoretical contributions, practical implications, and limitations are discussed.